Gender Relations and Gender Issues on Resource Management in the Central Cordillera, Northern Philippines - Brett, June Prill (Review of Women's Studies; Vol 14 No 1 (2004): Review of Women's Studies Volume XIV, Number 1 (January-June 2004), 2004)
This paper focuses on gender relations and issues in resource management among the Bontok, one of the several ethnolinguistic groups in the highlands of northern Philippines. the paper begins with a presentation of some theories and models on gender differences that have been assumed to be universally applicable. Most of these models try to explain gender differences in relation to female subordination and male domination. The Bontok case described in this paper shows that the theories on gender inequality, believed to be universal, are not supported, particularly when examining the gender division of labor and resource management in this highland society. Finally, some critical issues on gender concerns in upland resource management are presented, particularly in relation to government development programs/projects that often exclude and/or ignore women as equal partners in development planning and implementation.